The effects of cumulative risk and protection on problem behaviors for youth in an urban school-based system of care - Whitson, Melissa L.; Bernard, Stanley; Kaufman, Joy S. (Community Mental Health Journal, 2013)
The present study examined the cumulative effects of risk and protective factors on internalizing and externalizing problems for a sample of youth who were diagnosed with a severe emotional disturbance and enrolled in an urban school-based system of care. The sample included 139 Latino and African American children (ages 5-19; 65 % male) and their families. After controlling for demographic variables, the results of hierarchical multiple regression analyses revealed that cumulative risk and protection were significantly related to internalizing problem behaviors, and cumulative protection was negatively related to externalizing problem behaviors. The findings support the importance of including or increasing strength building approaches, in addition to risk reduction, in order to maximize prevention and intervention efforts for system-of-care populations.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-062-694-605-393 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Affective Symptoms; African American; African Americans; Child; Child; Preschool; Children's mental health; Cumulative protective factors; Cumulative risk factors; Female; Hispanic; Hispanic Americans; Humans; Internal-External Control; Internalizing and externalizing behavioral problems; Interviews as Topic; Male; Psychiatric Status Rating Scales; Questionnaires; Regression Analysis; Risk; Risk Factors; School Health Services; Schools; Severity of Illness Index; Social Behavior Disorders; Socioeconomic Factors; Systems of care; Urban Population; antisocial personality disorder; article; child; control; dept.swk; emotional disorder; female; human; interview; male; organization and management; peer-reviewed; preschool child; psychological aspect; psychological rating scale; questionnaire; regression analysis; risk; risk factor; school; school health service; severity of illness index; socioeconomics; statistics; urban population

Relationships between child emotional and behavioral symptoms and caregiver strain and parenting stress - Vaughan, Ellen L.; Feinn, Richard; Bernard, Stanley; Brereton, Maria; Kaufman, Joy S. (Journal of Family Issues, 2013)
Children with emotional and behavioral disturbance often have difficulties in multiple symptom domains. This study investigates the relationships between child symptoms and caregiver strain and parenting stress among 177 youth and their caregivers participating in a school-based system of care. Youth were grouped by symptom domain and included those with low scores on both internalizing and externalizing symptoms, those with only high internalizing symptoms, those with only high externalizing symptoms, and those with high symptoms levels in both internalizing and externalizing domains. Results revealed significant group differences on measures of caregiver strain and parenting stress. Caregivers of youth with symptoms in both internalizing and externalizing domains reported the highest levels of strain and stress; however, there was some variation in group differences by caregiver outcome. The results of this study emphasize the importance of providing not only services for youth but also support services for their caregivers.
65 citations (Crossref) [2023-10-31] tex.eissn: 1552-5481 tex.unique-id: ISI:000316914300005
Keywords: caregiver strain; dept.swk; parenting stress; peer-reviewed; serious emotional and behavioral disturbance